2018
DOI: 10.3390/genes9100477
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Survival Traits, Probiotic Determinants, Host Interactions, and Functional Evolution of Bifidobacterial Genomes Using Comparative Genomics

Abstract: Members of the genus Bifidobacterium are found in a wide-range of habitats and are used as important probiotics. Thus, exploration of their functional traits at the genus level is of utmost significance. Besides, this genus has been demonstrated to exhibit an open pan-genome based on the limited number of genomes used in earlier studies. However, the number of genomes is a crucial factor for pan-genome calculations. We have analyzed the pan-genome of a comparatively larger dataset of 215 members of the genus B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 139 publications
1
9
0
Order By: Relevance
“…Some highly conserved functional categories, such as translation, ribosomal structure and biogenesis (J, 12.71%), general function prediction only (R, 12.35%), function unknown (S, 10.45%), and amino acid transport and metabolism (E, 7.4%), were enriched among the core-genome of Lacticaseibacillus strains (Supplementary Figure 3). Translation functions are important for maintaining physiological parameters during changes to which gut microorganisms are exposed, suggesting their adaptive and survival roles (Sharma et al, 2018). Similar to our study, genomic analysis of Bifidobacterium showed high conservation of "Translation, ribosomal structure, and biogenesis (J)" class in the core-genome, demonstrating the importance of information storage for these bacteria to adapt and survive in the gut (Sharma et al, 2018).…”
Section: Comparative Genomic Analysis Of Lacticaseibacillus Strainssupporting
confidence: 82%
See 1 more Smart Citation
“…Some highly conserved functional categories, such as translation, ribosomal structure and biogenesis (J, 12.71%), general function prediction only (R, 12.35%), function unknown (S, 10.45%), and amino acid transport and metabolism (E, 7.4%), were enriched among the core-genome of Lacticaseibacillus strains (Supplementary Figure 3). Translation functions are important for maintaining physiological parameters during changes to which gut microorganisms are exposed, suggesting their adaptive and survival roles (Sharma et al, 2018). Similar to our study, genomic analysis of Bifidobacterium showed high conservation of "Translation, ribosomal structure, and biogenesis (J)" class in the core-genome, demonstrating the importance of information storage for these bacteria to adapt and survive in the gut (Sharma et al, 2018).…”
Section: Comparative Genomic Analysis Of Lacticaseibacillus Strainssupporting
confidence: 82%
“…Translation functions are important for maintaining physiological parameters during changes to which gut microorganisms are exposed, suggesting their adaptive and survival roles (Sharma et al, 2018). Similar to our study, genomic analysis of Bifidobacterium showed high conservation of "Translation, ribosomal structure, and biogenesis (J)" class in the core-genome, demonstrating the importance of information storage for these bacteria to adapt and survive in the gut (Sharma et al, 2018). In addition, for the accessory-genome and unique-genome, we observed enrichment of genes in the COG category "Carbohydrate transport and metabolism (G, 17.73-17.52%)."…”
Section: Comparative Genomic Analysis Of Lacticaseibacillus Strainsmentioning
confidence: 99%
“…The few studies that have considered the association between bifidobacteria diversity and their hosts and environments have found contradictory results. Some studies observe no relationship between hosts and the type of genes bifidobacteria carry [21,22], while others do [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly due to the exogenous protective effects accelerating the survival rate of the probiotic cells within the host gastrointestinal tract [79][80]78]. The metabolic substrates of the human milk oligosaccharides enhance the Bi dobacterial probiotic adhesions and colonisations to the host intestinal mucosa, especially during the host's early life [79][80][81]. In particular, members of the Bi dobacterium are among the key bacterial compontents (i.e., B. longum, B. dum, and B. breve species) of the infant intestines.…”
Section: Discussionmentioning
confidence: 99%